Understanding Impluse Buying in Tiktok Shop: An Investigation into Hedonic and Utilitarian Browsing in Indonesia - Azzahra, Gezha Meisya; Agus Setyawan, Anton (International Journal of Management Science and Information Technology, 2025)
With the rapid growth of social commerce, TikTok Shop has emerged as a leading mobile shopping platform that integrates entertainment with e-commerce. Understanding the factors driving impulse buying on this platform is essential for businesses and policymakers. While previous research highlights the role of browsing behavior in purchasing decisions, the influence of hedonic and utilitarian browsing on impulse buying remains underexplored. This study aims to analyze the relationship between hedonic and utilitarian browsing behavior on TikTok Shop and its impact on impulse buying tendencies. Specifically, it investigates the mediating role of utilitarian browsing and considers external factors such as mobility, visual appeal, and interpersonal influence. A quantitative survey was conducted in 2024 with 153 TikTok Shop users, and data were analyzed using SmartPLS 3.0 to examine the proposed relationships. The findings reveal that hedonic browsing significantly influences impulse buying, with utilitarian browsing acting as a mediator. Moreover, external factors, including mobility, visual appeal, and social influence, enhance consumer engagement and drive impulse purchases. These insights provide valuable implications for e-commerce businesses in optimizing marketing strategies through interactive content, social recommendations, and visually appealing elements. Policymakers can also leverage these findings to promote responsible shopping behavior. Future research should explore self-control mechanisms and long-term digital shopping trends to foster a more sustainable online shopping environment.